2014
DOI: 10.1186/1471-2148-14-60
|View full text |Cite
|
Sign up to set email alerts
|

Sensory trait variation in an echolocating bat suggests roles for both selection and plasticity

Abstract: BackgroundAcross heterogeneous environments selection and gene flow interact to influence the rate and extent of adaptive trait evolution. This complex relationship is further influenced by the rarely considered role of phenotypic plasticity in the evolution of adaptive population variation. Plasticity can be adaptive if it promotes colonization and survival in novel environments and in doing so may increase the potential for future population differentiation via selection. Gene flow between selectively diverg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 143 publications
(215 reference statements)
1
58
0
Order By: Relevance
“…This was also the case for R. ferrumequinum (Jiang et al., 2015) in Asia and for R. capensis in southern Africa. Similar to R. damarensis , R. capensis has a distribution that extends into the more arid western and northwestern regions of South Africa (Neumann & Bamford, 2015; Odendaal et al., 2014) and its RF was also not correlated with RH (Odendaal et al., 2014). This may be because both R. damarensis (Figure 5b) and R. capensis (Odendaal et al., 2014) occupy more arid regions (Table 1; compare with Mutumi et al., 2016) and in such areas temperature is a better predictor of RF than RH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was also the case for R. ferrumequinum (Jiang et al., 2015) in Asia and for R. capensis in southern Africa. Similar to R. damarensis , R. capensis has a distribution that extends into the more arid western and northwestern regions of South Africa (Neumann & Bamford, 2015; Odendaal et al., 2014) and its RF was also not correlated with RH (Odendaal et al., 2014). This may be because both R. damarensis (Figure 5b) and R. capensis (Odendaal et al., 2014) occupy more arid regions (Table 1; compare with Mutumi et al., 2016) and in such areas temperature is a better predictor of RF than RH.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed lineage diversification within species in the western half of southern Africa as a result of climate‐induced changes in biomes (Bauer & Lamb, 2005; Matthee & Flemming, 2002). Comparative studies in the western half of southern Africa revealed lineage diversification and clades within species in a wide range of animals such as reptiles (da Silva & Tolley, 2013), insects (Pitzalis & Bologna, 2010), and mammals (Matthee & Robinson, 1996; Willows‐Munro & Matthee, 2011; du Toit, Jansen Van Vuuren, Matthee, & Matthee, 2012) including horseshoe bats (Jacobs et al., 2013; Odendaal et al., 2014; Taylor et al., 2012). It appears therefore that local adaptation to climate in combination with an interruption of gene flow resulting from IbE may explain phenotypic divergence in R. damarensis and the regions fauna.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This species emits resting frequency echolocation calls (RF, calls emitted by rhinolophid bats when stationary and hunting from a perch; Neuweiler et al, 1987;Schnitzler, 1968) that vary by more than 10 kHz across its distribution range ( Fig. 1; Odendaal, Jacobs, & Bishop, 2014). The lowest resting peak frequency, 75 kHz, is found in the northwestern part of its distribution, and the highest, 86 kHz, in the southeast.…”
Section: Study Animalmentioning
confidence: 99%